A missão na cidade a partir do Documento de Aparecida - Leme, Paulo Sérgio (2016)
The city became the place itself of new cultures, scenario in which they are gener ated and impose themselves a new language and a new symbology. Sets up a new social structure of the Information Age, a company set up by production networks, power and experiences that build the virtual culture in global flows and that transcend time and space. Incarnated in this context, the Church in light of the Aparecida document is called to rethink deeply and relaunch with fidelity and courage its mission in the new circumstances Latin American and global. It is important to detect dynamics that run through and condition the Church's presence in the city. The pastoral action must be an expression of an understanding of the faith and the Church in the pluralistic and diverse context of today's reality, where the bulk of the city is to organize a genuine dialogue among all social categories. In this dialogue all can claim to force their participation in the city and reach higher levels of commitment, in order to overcome the challenges arising from structures that limit the actions and superficializam relations